2022
DOI: 10.1080/21655979.2022.2073128
|View full text |Cite
|
Sign up to set email alerts
|

LINC00313 regulates the metastasis of testicular germ cell tumors through epithelial-mesenchyme transition and immune pathways

Abstract: Testicular germ cell tumor (TGCT) is a relatively rare entity tumor, accounting for only 1% of all male cancers. However, it is the most common solid tumor in young men between 15 and 34 years old. Long noncoding RNAs (lncRNAs) are involved in various physiological and pathological processes. However, the functions of lncRNAs in TGCT have only rarely been investigated. LncRNAs associated with TGCT were identified using Gene Expression Omnibus (GEO) database and UCSC XENA database data mining. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Fifty non-redundant individual miRNAs or miRNA clusters targeting TCF7, 23 miRNAs targeting LINC00313 and 16 common miRNAs for the two transcripts were found. By searching the current literature for established associations between LINC00313 and miRNA, with a special interest on the 16 aforementioned predicted miRNAs, we observed that LINC00313 may induce cell migration and invasion, possibly by inducing β-catenin and EMT by sequestering miR-138-5p, miR-150-5p, miR-204-5p and miR-205-5p, which target the EMT-associated VIM and ZEB1 mRNAs (Liu et al, 2022a ). In addition, TCF7 could be transcriptionally regulated by β-catenin and TCF7L2 transcription factors (Zhu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty non-redundant individual miRNAs or miRNA clusters targeting TCF7, 23 miRNAs targeting LINC00313 and 16 common miRNAs for the two transcripts were found. By searching the current literature for established associations between LINC00313 and miRNA, with a special interest on the 16 aforementioned predicted miRNAs, we observed that LINC00313 may induce cell migration and invasion, possibly by inducing β-catenin and EMT by sequestering miR-138-5p, miR-150-5p, miR-204-5p and miR-205-5p, which target the EMT-associated VIM and ZEB1 mRNAs (Liu et al, 2022a ). In addition, TCF7 could be transcriptionally regulated by β-catenin and TCF7L2 transcription factors (Zhu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their up-regulation has been significantly correlated with poor overall survival. This correlation has been attributed to their role in modulating the expression of epithelial–mesenchyme transition (EMT)-related proteins, regulating High Mobility Group AT-Hook 2 (HMGA2), and activating Wnt/β-catenin signaling [ 30 , 31 , 32 ]. We observed that these lncRNAs were significantly up-regulated in FLC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TGCTs are caused by abnormal expression of genes that related to proliferation, pluripotency, and epigenetics. Our previous study found that several long non-coding RNAs (LncRNAs), including lncRNAs RFPL3S, LINC00313, and LINC00467, played important roles in TGCT proliferation, invasion, and functioned as prognostic biomarkers [ [7] , [8] , [9] ]. This indicates that long non-coding RNAs play an important role in the occurrence and development of TGCT.…”
Section: Introductionmentioning
confidence: 99%